Characteristic of Travertine Deposits: A Systematic Literature Review - Isman Saleh (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Travertine is a non-marine carbonate rock precipitated from calcium- and bicarbonate-rich waters, commonly associated with hot springs, streams, and lakes in tectonically active regions. This study presents a systematic literature review of travertine deposit characteristics, encompassing mineralogical composition, geochemical signatures, petrographic textures, morphological types, isotopic properties, biotic–abiotic controls on formation, early diagenesis, and petrophysical implications. The synthesis indicates that travertine is predominantly composed of calcite, with aragonite forming under conditions of elevated temperature, high Mg/Ca ratios, and rapid CO₂ degassing. Travertines display exceptional textural diversity, ranging from abiotic crystalline crusts to microbially mediated fabrics such as shrub, peloidal, and stromatolitic structures. Major morphologies include fissure ridges, mounds, terraces, cascades, and slopes, strongly governed by tectonic setting, topography, hydrology, and substrate geology. Stable isotopes (δ¹³C and δ¹⁸O), strontium isotopes, trace elements, and REE patterns effectively constrain fluid provenance and distinguish thermogene from meteogene travertines. Microbial activity plays a crucial role in biomineralization, influencing precipitation rates, crystal morphology, and lamination patterns. Early diagenetic processes occurring during active deposition may significantly modify primary fabrics and geochemical signals. Travertine petrophysical properties exhibit distinctive porosity–velocity relationships, making them valuable analogues for subsurface carbonate reservoirs. This review highlights that travertines record complex interactions among physical, chemical, biological, and geological processes and hold significant value for paleoenvironmental reconstruction and carbonate reservoir studies.